2004
DOI: 10.1536/jhj.45.637
|View full text |Cite
|
Sign up to set email alerts
|

<b>Effect of Renal Artery Stenting on Renal Function in Patients With Ischemic Nephropathy</b>

Abstract: SUMMARYThe aim of this study was to evaluate the effects of stenting on blood pressure and renal functions in azotemic patients with proximal/ostial atherosclerotic renal artery stenosis.Thirteen azotemic patients (5 females, 8 males, average age, 62.7 ± 8.3 years) who had renal artery stenosis were included in the study. Their blood pressure, estimated glomerular filtration rate (EGFR), and creatinine levels were measured at baseline and during follow-up.Stents were implanted successfully in all of the cases.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2005
2005
2010
2010

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
0
6
0
1
Order By: Relevance
“…[1][2][3] Because of its low morbidity and mortality, it usually results in better control of hypertension and leads to improvement or preservation of renal functions. Moreover, from recent reports, it has been clarified that primary renal stent placement is superior to renal balloon angioplasty alone in view of the angiographic results, the functional results, and vessel patency, particularly in ostial lesions characterized by a high restenosis rate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3] Because of its low morbidity and mortality, it usually results in better control of hypertension and leads to improvement or preservation of renal functions. Moreover, from recent reports, it has been clarified that primary renal stent placement is superior to renal balloon angioplasty alone in view of the angiographic results, the functional results, and vessel patency, particularly in ostial lesions characterized by a high restenosis rate.…”
Section: Discussionmentioning
confidence: 99%
“…The serum level of plasma renin activity was 2.70 ng/mL/ hour (normal range, 0.20-2.70). An ECG taken 18 years prior to admission was normal, whereas that taken on admission showed negative T waves in leads I, a VL, and V [1][2][3][4][5][6] . Two-dimensional transthoracic echocardiography revealed that the apical wall of the left ventricle was thin and dyskinetic, suggesting an apical old myocardial infarction.…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…Percutaneous transluminal renal angioplasty and stenting (PTRAS) is intended to replace open surgical revascularization operations as the treatment of choice for atherosclerotic renovascular disease (RVD) [13][14][15]. PTRAS is not only a less invasive procedure but is also associated with fewer complications and lower procedure-related mortality rates [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…During the last few years, percutaneous transluminal renal angioplasty (PTRA) with concomitant use of renal stenting (PTRAS) attempts to replace open surgical revascularization operations as the treatment of choice for atherosclerotic renovascular disease [11][12][13]. PTRAS is not only a less invasive procedure, but it is also associated with minimal complication and procedure-related mortality rates [14,15].…”
Section: Introductionmentioning
confidence: 99%